Extracellular vesicles compartment in liquid biopsies: Clinical application. (April 2018) - Garcia-Romero, Noemi; Esteban-Rubio, Susana; Rackov, Gorjana; Carrión-Navarro, Josefa; Belda-Iniesta, Cristobal; Ayuso-Sacido, Angel
Abstract: Liquid biopsy is becoming a new source of biomarkers that complement and resolve some of the most important limitations of surgical biopsy, which are the accessibility to the diseased tissue and its heterogeneity, especially relevant for tumors. The diseased tissues release their molecule content to the bloodstream in free form, inside a cell or within extracellular vesicles (EVs). While the identification of molecular alterations in total DNA isolated from peripheral blood is already in use for some tumors that secrete large amounts of DNA, it is challenging to assay those secreting lower amounts of molecules as well as for many other non-tumoral pathologies like immunological and cardiovascular diseases. In this scenery, the compartment of diseased tissue-derived EVs will be one of the best alternatives for the detection and identification of current and new biomarkers and targets in the clinical management of these diseases. Here, we review the mechanisms of molecular internalization as well as the correlation of EV's cargo with clinical parameters in tumor and non-tumor diseases, with special emphasis in clinical application.